PREFERRED LEADERSHIP STYLES FOR MILLENIALS GENERATION: A LITERATURE REVIEW - Lambok Nababan; Jhason Kristian Lee; Moh. Ali Al Kafit; M Firman Felani Hidayatullah (EKOBIS, 2024)
Each organization is expected to have a leader who is able to adapt his leadership style to the loyalty of the generations in the organization so that his leadership is considered the best leadership style. In this research, there are various leadership styles that are considered the closest to the millennial generation. The purpose of this research is to examine the ideal leadership style for the millennial generation. The types of leadership styles examined in this study are participative, adaptive, transformational, ethical/moral and laissez-faire leadership styles which were identified as the most prevalent styles and were assessed to explore how leadership styles approach the millennial generation. This research fills a gap in the literature and can provide guidance to leaders, with respect to each generation's preference for a particular leadership style. This research is a type of qualitative research with descriptive analysis techniques where this research uses literacy studies or literature reviews from various sources such as journals and books. The results of this study conclude that millennials have modern values and believe in treating everyone equally, despite the desire to be the center of attention to grab attention the show.